Latinx political cartooning during the COVID-19 global pandemic: coping and processing via Lalo Alcaraz's and Eric J. Garcia's social artivism. Issue 2 (3rd May 2020) - Rutherford, Jessica
ABSTRACT: This essay explores the way in which the political cartooning of Lalo Alcaraz and Eric J. García uses parody and satire, the stylistic linchpins of the genre, to help their followers process and cope with the physical and social disease brought on by the COVID-19 global pandemic. From their distinctly Chicanx perspectives, Alcaraz's and García's cartoons chronicle the way in which U.S. imperialism and neo-liberal socio-economic policies impact marginalized communities at home and around the globe, not only in their combination of text and image in their panels and strips, but also in the transcultural symbolism they draw from to depict U.S. politics and society. Because of the social artivism in which this work engages, it serves as a powerful shaping device, helping followers to process and cope with difficult realities while symbolically countering dominator discourse.